Effect of Gum Ashitaba (Angelica keiskei) on Slaughter Weights, Carcass Weights and Physical Quality of Broiler Meat - Mizan Azharis; Dina Oktaviana; Mashur Mashur (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
Ashitaba (Angelica keiskei) is an herbal plant that has many functions for the body. The purpose of this study to determine the increase in slaughter weight, carcass weight and physical quality of broiler meat. This study used 20 broiler chickens were grouped into 4 groups and each consisting of five chickens. The study design is completely randomized design (CRD) with design Randomized Post Test Only Control Group Design. The real difference between treatments was tested further using Duncan test. The study consists of four treatment that P1 (negative control without given any treatment, P2 ( positive control treatment with vitamin, antibiotics, vaccines and supplements), P3 (sap Ashitaba 2 ml/liter of water, and P4 (sap Ashitaba 4 ml/liter of water). The results showed that administration of sap Ashitaba a dose of 2 ml/liter can improve pH (p <0.05) but did not affect slaughter weight, carcass weight, water holding capacity and cooking losses broiler meat. Key word: Broilers, Gum Ashitaba, Carcass, Physical Quality of the Meat